2010
DOI: 10.2105/ajph.2010.192757
|View full text |Cite
|
Sign up to set email alerts
|

Using Geographic Information Systems and Local Food Store Data in California's Low-Income Neighborhoods to Inform Community Initiatives and Resources

Abstract: Objectives. We examined conditions in California low-income neighborhoods that affect obesity to inform program planning, nutrition education, community participation, investment of resources, and involvement of stakeholders. Methods. Staff members in 18 local health departments were trained to use an online geographic information system (GIS) and conduct field surveys. GIS data were aggregated from 68 low-income neighborhoods of 1 or more census tracts. Data were collected in 2007 to 2009 from 473 grocery st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 18 publications
(16 reference statements)
1
38
1
2
Order By: Relevance
“…Several of the studies have found that minorities are more likely to consume toxic food than are Whites~Beehler, Vena, 2001, 2003;Calderon et al, 1993;Chess, Burger, and McDermott, 2005;Hightower, O'Hare, and Hernandez, 2006;Judd, O'Neil, and Kalman, 2003;LaDuke, 1999;Madsen et al, 2007;Nordenstam and Darkwa, 2010;Pallo and Barken, 2010;Sechena et al, 2003;West, 1992;West et al, 1992!. The studies have also found that food costs more in neighborhoods described as food deserts~Alaimo, Reischl, and Allen, 2010;Bacolor, Guzmán, and Waller, 2007;Beaulac, Kristjansson, and Cummins, 2009;Chung and Myers, 1999;Gallagher, 2006Gallagher, , 2007Gottlieb and Fisher, 1996;Helling and Sawicki, 2003;Hinrichs and Allen, 2008;Laraia et al, 2004;Liese et al, 2010;Levkoe, 2006;Morland et al, 2002;Nord, Andrews, and Carlson, 2008;Pothukuchi, 2005;Seligman, Laraia, and Kushel, 2010;Sharkey and Horel, 2008;Walker, Keane, and Burke, 2010;Wrigley et al, 2002;Zenk et al, 2005Zenk et al, , 2006Zenk et al, , 2009 However, some researchers question whether food deserts exist, finding food environments instead in which a variety of food outlets serve poor, innercity neighborhoods~Ghirardelli, Quinn, and Foerster, 2010;Raja, Ma, and Yadav, 2008;…”
Section: Case Studies Toxic Food Consumption and Occupational Safetymentioning
confidence: 99%
“…Several of the studies have found that minorities are more likely to consume toxic food than are Whites~Beehler, Vena, 2001, 2003;Calderon et al, 1993;Chess, Burger, and McDermott, 2005;Hightower, O'Hare, and Hernandez, 2006;Judd, O'Neil, and Kalman, 2003;LaDuke, 1999;Madsen et al, 2007;Nordenstam and Darkwa, 2010;Pallo and Barken, 2010;Sechena et al, 2003;West, 1992;West et al, 1992!. The studies have also found that food costs more in neighborhoods described as food deserts~Alaimo, Reischl, and Allen, 2010;Bacolor, Guzmán, and Waller, 2007;Beaulac, Kristjansson, and Cummins, 2009;Chung and Myers, 1999;Gallagher, 2006Gallagher, , 2007Gottlieb and Fisher, 1996;Helling and Sawicki, 2003;Hinrichs and Allen, 2008;Laraia et al, 2004;Liese et al, 2010;Levkoe, 2006;Morland et al, 2002;Nord, Andrews, and Carlson, 2008;Pothukuchi, 2005;Seligman, Laraia, and Kushel, 2010;Sharkey and Horel, 2008;Walker, Keane, and Burke, 2010;Wrigley et al, 2002;Zenk et al, 2005Zenk et al, , 2006Zenk et al, , 2009 However, some researchers question whether food deserts exist, finding food environments instead in which a variety of food outlets serve poor, innercity neighborhoods~Ghirardelli, Quinn, and Foerster, 2010;Raja, Ma, and Yadav, 2008;…”
Section: Case Studies Toxic Food Consumption and Occupational Safetymentioning
confidence: 99%
“…Improving the availability of nutritious food items and fresh foods at small grocery, convenience, and specialty food stores is a promising approach for improving community nutrition environments in underserved communities (26). The national Healthy Food Financing Initiative allocated more than $400 million in 2011 to fund local, state, and regional collaborations that expand access to nutritious foods (27).…”
Section: Discussionmentioning
confidence: 99%
“…Such temporal variations in the availability of healthy food can inform the policy debates surrounding healthy food access in America and are novel approaches to discerning access in particular geographies. Ghirardelli, Quinn, and Forester (2010) studied access to fresh produce in sixty-eight low-income neighborhoods in California with the intent of informing both formal and informal policies surrounding fresh produce access at the neighborhood level. The maps produced by Raja, Ma, and Yaday's (2008) Hwang and Smith (2012) developed a framework that utilizes publicly available mapping and open sourced software 3 that can be used to assess and map food security, showing that such projects can be undertaken at minimal cost and with relative ease in dissemination.…”
Section: Applicationsmentioning
confidence: 99%